ANALISIS PENGARUH CAPM BETA, FIRM SIZE, BOOK TO MARKET RATIO, DAN MOMENTUM TERHADAP RETURN SAHAM - Alex Tumpal Hutajulu; Evita Puspitasari (JAF (Journal of Accounting and Finance), 2019)
This research is performed to examine influence of capm beta, firm size, book to market ratio, and momentum on stock return in companies that listed on the Indonesia Stock Exchange. The population in this research was manufacture companies that listed on the Indonesia Stock Exchange during 2012-2014 with purposive sampling. Variables used in this research are capital gain (return), natural logarithma total asset (firm size), the ratio of book value to market value (book to market ratio), and return t-12 (momentum). The results shows that beta, firm size, book to market ratio and momentum simultaneously have a significant impact toward stock return. The conclusion based on partial test are (1) book to market ratio and momentum have a positive significance influence toward stock return (2) beta has negative insignificance influence toward stock return and firm size has positive insignificance influence toward stock return. Predictive capability of independent variabel in this research to stock return is 34,09% while other 65,91% was influenced by other factors.